2016
DOI: 10.4049/jimmunol.1600811
|View full text |Cite
|
Sign up to set email alerts
|

Type I CD20 Antibodies Recruit the B Cell Receptor for Complement-Dependent Lysis of Malignant B Cells

Abstract: Human IgG1 type I CD20 Abs, such as rituximab and ofatumumab (OFA), efficiently induce complement-dependent cytotoxicity (CDC) of CD20 B cells by binding of C1 to hexamerized Fc domains. Unexpectedly, we found that type I CD20 Ab F(ab') fragments, as well as C1q-binding-deficient IgG mutants, retained an ability to induce CDC, albeit with lower efficiency than for whole or unmodified IgG. Experiments using human serum depleted of specific complement components demonstrated that the observed lytic activity, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 34 publications
2
32
0
Order By: Relevance
“…control, to investigate the contribution of the BCR in anti-CD20-mediated complementdependent cytotoxicity (CDC) that we proposed (1). We agree with the notion that loss of accessory CDC after BCR knockout would provide additional evidence for the recruitment and activation of complement by CD20-mediated BCR clustering.…”
supporting
confidence: 74%
“…control, to investigate the contribution of the BCR in anti-CD20-mediated complementdependent cytotoxicity (CDC) that we proposed (1). We agree with the notion that loss of accessory CDC after BCR knockout would provide additional evidence for the recruitment and activation of complement by CD20-mediated BCR clustering.…”
supporting
confidence: 74%
“…W e read with great interest the article by Engelberts and colleagues (1), which concludes that presence of the BCR on a CD20-expressing cell line can render these cells susceptible for lysis via a type I Ab with a missing or defective C1q binding site. This phenomenon was termed accessory complement-dependent cytotoxicity (CDC).…”
mentioning
confidence: 99%
“…Thus, IgA2 and IgG1 differed in the types of effector cells they recruited (MNC versus PMN), and in the conditions under which they activated the complement pathway. Recent studies demonstrated that different CD20 antibody constructs, which cannot bind C1q themselves, recruited the surface immunoglobulin of B cells for C1q binding (Engelberts et al , ) – a mechanism that could also explain CDC by IgA antibodies.…”
mentioning
confidence: 99%